THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN PRIMARY SCHOOLS IN KENDARI CITY, SOUTHEAST SULAWESI PROVINCE - Adindo, Apri Winge (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to describe the implementation of inclusive education in primary school learning in Kendari City, Southeast Sulawesi Province. The object of the research is the primary school learning process in Kendari City, Southeast Sulawesi Province. This research used a qualitative approach with a case study research type. Research data were obtained through interviews, observations, and documentation. The collected data were analyzed descriptively using an interactive analysis model. The research data were tested for validity using extension of participation, persistence of observation, and triangulation. The results showed that the implementation of inclusive education in primary school learning in Kendari City, Southeast Sulawesi Province, has not been optimal in serving all the needs of students regardless of any differences. This can be seen from: 1. The chosen model for providing education for children with disabilities in some primary schools in Kendari city, Southeast Sulawesi province, is an integrated inclusive school. 2. The implementation of learning for children with disabilities for all primary schools in Kendari City, Southeast Sulawesi Province, which implement inclusive education with an integrated inclusive school model, in terms of the learning process, still uses the curriculum, infrastructure, teaching, and education personnel, learning media, and the grade promotion system and learning outcomes report system still use the regular system for all students.